Zakat Penghasilan Sebagai Pengurang Penghasilan Kena Pajak - Safarni Husain (Jurnal Risalah Hukum, 2010)
The existence and dualism of tax an zakat causes Moslems bear a heavy burden than non-Moslems people. To anticipate them at least there are three attitudes for which the Moslems have. First, by paying tax and zakat in the same time wealth become bigger as a risk. Second, thus tax and zakat are equal as the payment of zakat which they intend. Third, zakat payment without tax takes the risk of conflicting state laws. In essence, the maximizing of zakat donation and tax may give positive impact and great contribution on the development of Indonesia in order to produce a prosperous and wealthy community.